Proposed Action of Supply Chain Risk Mitigation Air Compressor Type L Unloading ¼ HP Using The Fuzzy – FMEA and Fuzzy – AHP Method in PT. XYZ - Dyah Lintang Trenggonowati; Achmad Bahauddin; Asep Ridwan; Yuyun Wulandari (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2021)
Established since the 80s, PT. XYZ is an air compressor manufacturing industry located in Tangerang, Indonesia. In the production process, the Air compressor type L Unloading 1/4 HP has a very complex supply chain network which makes the supply chain network activities experience obstacles in the form of risks or potential risks that can occur so that it can disrupt the smooth running of the supply chain activities of the air compressor type L. Unloading 1/4 HP. However, PT. XYZ has not maximally implemented risk mitigation actions in its supply chain. The purpose of this study is to propose a mitigation action against risk events that occur along the supply chain of water compressor type L Unloading 1/4 HP using the FFMEA (Fuzzy Failure Mode and Effect Analysis) and FAHP (Fuzzy Analytical Hierarchy Process) methods. Based on the research, there were 29 identified risk events with 5 priority risk events. And of the 5 priority risk events, each has 2 proposed mitigation actions per priority risk event